Heteroepitaxial Growth of Nonpolar (11\(2\)0)-Plane GaN Film via Composite Buffer Layer for the Promising Nonpolar GaN-based Devices - Jianguo Zhao; Boyan Suo; Ru Xu; Tao Tao; Zhe Zhuang; Bin Liu; Xiong Zhang; Jianhua Chang (Current Innovations in Chemical and Materials Sciences Vol. 5, 2024)
The development of semipolar/nonpolar structures was lagged behind the development of polar structures. In this study, several nonpolar (11\(2\) 0) a-plane GaN films were grown on semipolar (1\(1\)02) r-plane sapphire substrates using various buffer layers within a low-pressure metal organic chemical vapor deposition system. The structural properties of nonpolar a-plane GaN films were intensively investigated by the X-ray diffraction and Raman scattering measurements. A set of buffer layers were adopted from a GaN layer to a composite layer containing a multiple AlN layer and an Al composition graded AlGaN layer, the full width at half maximum of the X-ray rocking curves measured along the [0001]- and (10\(1\)0) -directions of a-plane GaN were reduced by 35% and 37%, respectively. It was also found that an order of magnitude reduction in the basal-plane stacking faults (BSFs) density can be reduced by the heterogeneous interface introduced with the composite buffer layer together. Moreover, the in-plane strains along c- and m-directions were increased from -0.326% and 0.121% to -0.388% and 0.288% when the buffer layer was changed from GaN to AlN, while they were further reduced to -0.107% and 0.137% when the buffer layer was replaced by the composite layer. A BSFs density as low as 2.95×104 cm-1, and a pit-free surface morphology were achieved for the a-plane GaN film grown with the composite buffer layer, which is promising for the development of nonpolar GaN-based devices in the future. This work provides promising insights for the development of nonpolar GaN-based LEDs with high-bandwidth for optical communications and microdisplays in the future.